Social support for cancer patients and alcohol and tobacco use: an integrative review - Juliana Benevenuto Reis; Karina Dal Sasso Mendes; Rogério Adriano Bosso; Natália Priolli Jora Pegoraro; Márcia dos Santos; Sandra Cristina Pillon (Universidade Federal do Ceará, 2024)
Objective: to assess the knowledge about social support and mental health of people diagnosed with cancer, smokers, and alcohol users, and the implications of these behaviors for cancer treatment. Methods: integrative review using the following databases: CINAHL, Embase, LILACS, PsycINFO, MEDLINE, SCOPUS, and Web of Science, without restriction of period and language. The data was analyzed descriptively. Results: 3,010 documents were identified, 14 studies were eligible. The different types of social support received by people with cancer and a history of alcohol and tobacco use stand out: emotional (n=5), informational (n=4), family and material (n=2 each), religious, sexual-affective partner, tangible, affective, positive social interaction, instrumental and social companionship (n=1 each). Conclusion: targeted social support that is sensitive to the particularities of the history of substance use can significantly improve the way people cope with the disease and treatment. Contributions to practice: providing integrated social support for this population is essential for thinking about quality of life throughout treatment and recovery.